The HSE X International Academic Conference on Economic and Social Development - Нет, Нет (Foresight and STI Governance, 2009)
In April 2009, Higher School of Economics held the 10th annual International Academic Conference on Economic and Social Development. Within the framework of the event, a separate section was organized by the HSE Institute for Statistical Studies and Economics of Knowledge (ISSEK) and the International Foresight Centre — “Innovation development of Russia’s economy: issues and lessons” which combined two sessions: “Science and Innovation in Russia: Results of Latest Years” and “Long-term Prospects of Innovation Development in Russia”.